1976
DOI: 10.1111/j.1365-2265.1976.tb01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Hypoparathyroidism and Parathyroid Hormone End‐organ Resistance in Human Magnesium Deficiency

Abstract: Hypocalcaemia is a well-recognized manifestation of magnesium deficiency. We have studied seventeen patients with this syndrome in an attempt to determine the pathogenesis of the hypocalcaemia. Mean initial serum calcium concentration was 5-6 mg/dl and mean initial serum magnesium concentration was 0-75 mg/dl. Serum immunoreactive parathyroid hormone (IPTH) was measured in sixteen patients in the untreated state. Despite severe hypocalcaemia, serum IPTH was either undetectable (less than 150 pg/ml) or normal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
157
0
3

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(165 citation statements)
references
References 51 publications
5
157
0
3
Order By: Relevance
“…Impaired secretion of PTH caused by reduction in serum Mg levels has been thought to be one of the major mechanisms by which hypocalcemia develops in Mg deficiency [3][4][5][6][7]. PTH secretion is known to be affected by extracellular Mg in vitro [24] and in vivo [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Impaired secretion of PTH caused by reduction in serum Mg levels has been thought to be one of the major mechanisms by which hypocalcemia develops in Mg deficiency [3][4][5][6][7]. PTH secretion is known to be affected by extracellular Mg in vitro [24] and in vivo [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that serum PTH concentration was suppressed in patients with hypomagnesemia [4,5], and Mg substitution therapy enhanced PTH secretion and reversed PTH target-organ resistance, and thus serum calcium concentration returned to normal within several days [4,7]. In addition, Mg deficiency could inhibit the synthesis of 1,25-dihydroxy vitamin D (1,25(OH) 2 D) [9][10][11] as well as its action on bone [11].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been known for many years that magnesium (Mg) deficiency leads to an increase in serum PTH, which promotes calcium (Ca) release from bone (Rude et al, 1976). More recently Mg deficiency for just 3 weeks in young, growing rats has been shown to lead to decreased bone turnover that could impair bone growth and development (Creedon et al, 1999).…”
Section: Introductionmentioning
confidence: 99%